Efficacy and safety of PD-1/PD-L1 inhibitors combined with tyrosine kinase inhibitors as first-line treatment for hepatocellular carcinoma: a meta-analysis and trial sequential analysis of randomized controlled trials - Tang, Peng; Zhou, Fei (Frontiers in Pharmacology, 2025)
BackgroundThe use of immune checkpoint inhibitors (ICIs) in treating hepatocellular carcinoma (HCC) has grown significantly. However, the therapeutic benefits of ICIs alone are notably modest. This meta-analysis assesses the efficacy and safety of using PD-1/PD-L1 inhibitors in conjunction with tyrosine kinase inhibitors (TKIs) for patients with advanced or unresectable HCC.MethodsAn extensive search of the literature was performed using databases such as PubMed, Web of Science, Embase, and the Cochrane Library, capturing randomized controlled trials (RCTs) until 16 October 2024. Efficacy was measured by progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR). Safety was gauged through the occurrence of treatment-related adverse events (TRAEs). Hazard ratios (HRs) for PFS and OS, along with risk ratios (RRs) for ORR, DCR, and TRAEs, were calculated, each with 95% confidence intervals (CIs). Heterogeneity among studies was quantified using Cochran’s Q test, I2 statistics, and 95% prediction intervals (PIs).ResultsThis analysis incorporated 4 studies with a total of 2,174 patients. Treatment regimens combining PD-1/PD-L1 inhibitors with TKIs significantly improved PFS (HR = 0.694, 95% CI: 0.527–0.914; 95% PI: 0.228–2.114) and ORR (RR = 2.303, 95% CI: 1.360–3.902; 95% PI: 0.408–12.991) compared with first-line monotherapy or TKI monotherapy in the overall population. Subgroup analysis indicated that the improvements in PFS and OS were particularly significant among patients of Asian descent or those with hepatitis B virus (HBV) infection (all p < 0.05). While the occurrence of any grade TRAEs did not differ significantly between the two groups (RR = 1.016, 95% CI: 0.996–1.036; 95% PI: 0.941–1.097), the incidence of serious (RR = 2.068, 95% CI: 1.328–3.222; 95% PI: 0.487–8.776) and grade ≥3 TRAEs (RR = 1.287, 95% CI: 1.020–1.624; 95% PI: 0.574–2.883) increased in patients treated with the combination of PD-1/PD-L1 inhibitors and TKIs.ConclusionThis study revealed that combining PD-1/PD-L1 inhibitors with TKIs in the treatment of advanced or unresectable HCC leads to superior clinical outcomes compared to first-line monotherapy or TKIs alone, particularly in patients with HBV infection and those of Asian descent. Clinicians are advised to be vigilant regarding the potential for TRAEs in clinical settings.